Cardiac Troponin‐I Concentration, Myocardial Arteriosclerosis, and Fibrosis in Dogs with Congestive Heart Failure because of Myxomatous Mitral Valve Disease. (3rd April 2013) - Falk, T.; Ljungvall, I.; Zois, N.E.; Höglund, K.; Olsen, L.H.; Pedersen, H. D; Häggström, J.
<x xml:space="preserve">Abstract</x> Background Few previous studies have investigated the association between biomarkers and cardiac disease findings in dogs with naturally occurring myxomatous mitral valve disease (MMVD). Aim To investigate if histopathological changes at necropsy could be reflected by in vivo circulating concentrations of cTnI and aldosterone, and renin activity, in dogs with naturally occurring congestive heart failure because of MMVD. Animals Fifty privately owned dogs with MMVD and heart failure. Methods Longitudinal Study. Dogs were prospectively recruited and examined by clinical and echocardiographical examination twice yearly until time of death. Blood was stored for batched analysis of concentrations of cTnI and aldosterone, and renin activity. All dogs underwent a standardized necropsy protocol. Results cTnI were associated with echocardiographic left ventricular end‐diastolic dimension (P < .0001) and proximal isovolumetric surface area radius (P < .004). Furthermore, in vivo cTnI concentrations reflected postmortem findings of global myocardial fibrosis (P < .001), fibrosis in the papillary muscles (P < .001), and degree of arterial luminal narrowing (P < .001) Aldosterone or renin activity did not reflect any of the cardiac disease variables investigated. Conclusion and clinical importance Cardiac fibrosis and arteriosclerosis in dogs with MMVD are reflected by circulating cTnI concentration, but not by aldosterone concentration or renin activity. Cardiac troponin I could be a valuable biomarker for myocardial fibrosis in dogs with chronic cardiac diseases.